SCREENING OF IMMUNOMODULATORY EFFICIENCY OF LAURUS NOBILIS - SUGANTHI. R; R. ARUNKUMAR (International Journal of Pharma and Bio Sciences, 2014)
Medicinal plants have an important role in our normal life. The plant immunostimulant activity was screened using animal modal. The efficiency of immunostimulant was analysed antibody titration, B and T cell counts and differential count method. From the results the antibody levels were significantly raised compared to pathogen treated animal. The T cell counts were increased due to the cellular level stimulation of plant extract in host. In the present investigation concluded that the plant extracts of L. nobilis have immunostimulant potential.